2016
DOI: 10.1097/md.0000000000004504
|View full text |Cite
|
Sign up to set email alerts
|

Transseptal puncture by CTP-2 method

Abstract: The current used parameters for transseptal puncture (TSP) under fluoroscopic guidance is from left atriography and need to be verified by precise anatomic measurement. From February 2009 to July 2013, consecutive patients who received computed tomography (CT) were included. Landmarks and parameters were preliminary studied by right atriography, and further evaluated on the CT images of 1001 patients. A method (CTP-2) was proposed for guiding TSP. In right anterior oblique 45° view, the CTP-2 method was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…TSP could result in life‐threatening complications and was traditionally conducted at 40° in RAO projection. Previous study showed that the best angle for projecting the septum was RAO 36° 6 . However, according to the present study, the orientation of the IAS varies widely, ranging from 16° to 53°, which poses challenges to the traditional practice of TSP with fixed RAO X‐ray projection.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…TSP could result in life‐threatening complications and was traditionally conducted at 40° in RAO projection. Previous study showed that the best angle for projecting the septum was RAO 36° 6 . However, according to the present study, the orientation of the IAS varies widely, ranging from 16° to 53°, which poses challenges to the traditional practice of TSP with fixed RAO X‐ray projection.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we reported a novel and easy way to adjust the projection of X‐ray during TSP procedural according to the IAS orientation measured from the MDCT scan. There was also other MDCT‐guided method reported previously 6 . However, with only one plane to determine the angulation, our method is more straightforward.…”
Section: Discussionmentioning
confidence: 89%
“…Как уже указывалось выше, для определения направления иглы для пункции МПП может быть использован такой ориентир, как катетер в КС. Однако, необходимо подчеркнуть, что в доступной литературе лишь немногими была изучена взаимосвязь между МПП и КС [11,12]. В нашей работе было впервые изучено взаимоотношение этих анатомических структур у пациентов, которым в последующем выполнялась КБИ УЛВ.…”
Section: обсуждение полученных результатовunclassified
“…В то же время метод, предложенный Y. Wang et al (2016) [12] для определения оптимального места пункции МПП под рентгеноскопическим контролем, использует как точку отсчёта место бифуркации средней вены сердца в КС. Согласно авторам, наиболее подходящая точка для пункции находилась в середине МПП, в её наиболее широкой части.…”
Section: обсуждение полученных результатовunclassified
See 1 more Smart Citation